Mixed method evaluation of a learning from excellence programme for community health workers in Neno, Malawi - Maartje Kletter; Bronwyn Harris; Emilia Connolly; Chifundo Namathanga; Basimenye Nhlema; Henry Makungwa; Benson Chabwera; Benson Phiri; Celia Brown (BMC, 2024)
Abstract Background Community Health Workers (CHWs) play an essential role in linking communities to facility-based healthcare. However, CHW programmes have often been hampered by low levels of staff motivation, and new tools aimed at improving staff motivation and work environment are needed. One such intervention is the "Learning from Excellence" (LfE) programme. We aimed to assess feasibility, outputs, and impact of a co-designed LfE programme on CHW motivation, in Neno District. Methods We conducted a convergent mixed-method evaluation of the LfE programme. Co-design of the programme and forms took place between October 2019 and January 2020. LfE forms submitted between September and November 2020 were analysed using descriptive statistics and memos summarising answers to the open-ended question. To investigate experiences with LfE we conducted in-depth semi-structured interviews with key stakeholders, CHWs, and site supervisors, which were analysed thematically. A pre-post intervention questionnaire was developed to assess the impact of the co-designed LfE intervention on CHW motivation and perceived supervision. Outcomes were triangulated into a logic model. Results In total 555 LfE forms were submitted, with 34.4% of CHWs in Neno District submitting at least one LfE report. Four themes were identified in the interviews: LfE implementation processes, experience, consequences, and recommendations. A total of 50 CHWs participated in the questionnaire in January 2020 and 46 of them completed the questionnaire in December 2020. No statistically significant differences were identified between pre-and post-LfE measurements for both motivation (Site F: p = 0.86; Site G: p = 0.31) and perceived supervision (Site F: p = 0.95; Site G: p = 0.45). A logic model, explaining how the LfE programme could impact CHWs was developed. Conclusions Many CHWs participated in the LfE intervention between September 2020 and November 2020. LfE was welcomed by CHWs and stakeholders as it allowed them to appreciate excellent work in absence of other opportunities to do so. However, no statistically significant differences in CHW motivation and perceived supervision were identified. While the intervention was feasible in Neno District, we identified several barriers and facilitators for implementation. We developed a logic model to explain contextual factors, and mechanisms that could lead to LfE outcomes for CHWs in Neno District. The developed logic model can be used by those designing and implementing interventions like LfE for health workers.